Pengaruh Peran Sektor Non-Pertanian, Kualitas Sumber Daya Manusia, dan Kesempatan Kerja terhadap Tingkat Kemiskinan - Purba, Yofa Selvida Theresia; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The purpose of this study was to determine the direct effect of the role of non-agricultural sector, the quality of human resources and employment to poverty and indirect influence of the role of non-agricultural sector and the quality of human resources against poverty through employment. This research was conducted in all districts/municipalities in Bali Province. The data used in this research is secondary data. Data collection was conducted using non-participant observation, while the analysis method used is the analysis of lane or path analysis. The analysis showed the role of the non-agricultural sector has a direct positive effect on employment, while the quality of human resources has no effect on employment. The role of the non-agricultural sector and the quality of human resources has a direct negative effect on poverty levels, while employment has a direct positive effect on poverty levels with Rm2 value of 0.848, which means that a variety of data can be explained by the model of 84.8 percent.
Keywords: Role of Non-Agricultural Sector; Quality of Human Resources; Employment; Poverty Rate